2017
DOI: 10.1117/12.2258126
|View full text |Cite
|
Sign up to set email alerts
|

Advanced development techniques for metal-based EUV resists

Abstract: Pure thin-films of unimolecular organometallic photoresists were lithographically evaluated using extreme ultraviolet light (EUV, λ = 13.5 nm) and developed using solutions containing carboxylic acids. Optimization of development solutions used with a cobalt-oxalate EUV resist (NP1, 2) led to a switch in lithographic tone from negative to positive. Additional optimization led to an improvement in top loss (35 to 7%) with development in cyclohexanone and 2-butanone, respectively. We saw a drastic improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The proposed photoproduct has been synthesized in literature 22 . These three compounds are typically negative tone when developed with simple organic solvents, though recent work has demonstrated that positive tone behavior can be achieved through specialized development 23 . Two trends seem to correlate with the increase in sensitivity, the increase in EUV absorption in the order of Cr < Fe < Co (Sec.…”
Section: Cr2+mentioning
confidence: 99%
“…The proposed photoproduct has been synthesized in literature 22 . These three compounds are typically negative tone when developed with simple organic solvents, though recent work has demonstrated that positive tone behavior can be achieved through specialized development 23 . Two trends seem to correlate with the increase in sensitivity, the increase in EUV absorption in the order of Cr < Fe < Co (Sec.…”
Section: Cr2+mentioning
confidence: 99%
“…Metal oxide resists (MORs) were the most interesting ones among them as the metals have high EUV absorption . Several resist platforms with high EUV absorption cross section, containing metals such as Sn, Hf, Zr, and Sb, have also been reported. Apart from high absorption, the ligands around the metal core in MOR offer numerous reaction sites which can increase sensitivity by the efficient use of secondary electrons. They showed resolution down to 10 nm using a 0.5 numerical aperture (NA) Berkeley microfield exposure tool (BMAT) and interference lithography. , However, due to the presence of moisture in ambient, the critical dimensions (CD) printed with MOR vary from wafer to wafer .…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide photoresists are potential candidates for the next generation; however, the conventional developer is not applicable to the development process for metal oxide photoresists. 8,9) On the other hand, TMAH is highly toxic to organisms. In previous research studies, aqueous solutions of other tetraalkylammonium hydroxides (TAAHs), such as tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TProAH), and tetrabutylammonium hydroxide (TBAH), were applied to the development of CARs to study the dissolution dynamics.…”
Section: Introductionmentioning
confidence: 99%